Decoding systems biology of inflammation signatures in cancer pathogenesis: Pan-cancer insights from 12 common cancers - TURANLI, BESTE (My University, 2023)
Chronic inflammation is an important contributor to tumorigenesis in many tissues. However, the underlying mechanisms of inflammatory signaling in the tumor microenvironment are not yet fully understood in various cancers. Therefore, this study aimed to uncover the gene expression signatures of inflammation-associated proteins that lead to tumorigenesis, and with an eye to discovery of potential system biomarkers and novel drug candidates in oncology. Gene expression profiles associated with 12 common cancers (e.g., breast invasive carcinoma, colon adenocarcinoma, liver hepatocellular carcinoma, and prostate adenocarcinoma) from The Cancer Genome Atlas were retrieved and mapped to inflammation-related gene sets. Subsequently, the inflammation-associated differentially expressed genes (i-DEGs) were determined. The i-DEGs common in all cancers were proposed as tumor inflammation signatures (TIS) after pan-cancer analysis. A TIS, consisting of 45 proteins, was evaluated as a potential system biomarker based on its prognostic forecasting and secretion profiles in multiple tissues. In addition, i-DEGs for each cancer type were used as queries for drug repurposing. Narciclasine, parthenolide, and homoharringtonine were identified as potential candidates for drug repurposing. Biomarker candidates in relation to inflammation were identified such as KNG1, SPP1, and MIF. Collectively, these findings inform precision diagnostics development to distinguish individual cancer types, and can also pave the way for novel prognostic decision tools and repurposed drugs across multiple cancers. These new findings and hypotheses warrant further research toward precision/personalized medicine in oncology. Pan-cancer analysis of inflammatory mediators can open up new avenues for innovation in cancer diagnostics and therapeutics.
Keywords: Tıp; Dahili Tıp Bilimleri; Tıbbi Genetik; Yaşam Bilimleri; Biyoteknoloji; Moleküler Biyoloji ve Genetik; Sitogenetik; Sağlık Bilimleri; Temel Bilimler; Medicine; Internal Medicine Sciences; Medical Genetics; Life Sciences; Biotechnology; Molecular Biology and Genetics; Cytogenetic; Health Sciences; Natural Sciences; Yaşam Bilimleri (LIFE); Mikrobiyoloji; BİYOKİMYA VE MOLEKÜLER BİYOLOJİ; BİYOTEKNOLOJİ VE UYGULAMALI MİKROBİYOLOJİ; GENETİK VE KALITIM; Life Sciences (LIFE); MOLECULAR BIOLOGY & GENETICS; MICROBIOLOGY; BIOCHEMISTRY & MOLECULAR BIOLOGY; BIOTECHNOLOGY & APPLIED MICROBIOLOGY; GENETICS & HEREDITY; Biyokimya; Moleküler Tıp; Moleküler Biyoloji; Genetik; Biochemistry; Molecular Medicine; Molecular Biology; Genetics; biomarker; drug repurposing; pan-cancer; personalized medicine; systems inflammation; the Cancer Genome Atlas